2018
DOI: 10.1159/000487391
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Safety of Pylera® in Patients Infected by <b><i>Helicobacter Pylori</i></b>: A Multicenter, Retrospective, Real Life Study

Abstract: Background: Our aims were to assess the real life effectiveness and safety of the new bismuth-containing quadruple therapy in a large population of patients infected by Helicobacter pylori. Methods: Consecutive dyspeptic H. pylori-positive patients were enrolled, both naïve for treatment and already unsuccessfully treated. Patients were treated with Pylera® 3 capsules 4 times/daily plus omeprazole 20 mg or esomeprazole 40 mg 2 times/daily for 10 days. Eradication was confirmed using a urea-breath test (at leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 22 publications
3
9
0
1
Order By: Relevance
“…Overall, of the 57 relevant references initially identified, 30 studies met the inclusion criteria and were included in the systematic review and meta‐analysis (Figure ). During the full‐text review stage, the authors of five primary studies were contacted for data clarification.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, of the 57 relevant references initially identified, 30 studies met the inclusion criteria and were included in the systematic review and meta‐analysis (Figure ). During the full‐text review stage, the authors of five primary studies were contacted for data clarification.…”
Section: Resultsmentioning
confidence: 99%
“…These differences in the efficacy of BQT (single capsule) plus a PPI were significant for the different lines of treatment evaluated (test for subgroup differences P < 0.001 and I 2 = 74%). Almost all studies reported PP eradication rates but in four studies, and could not be computed. The overall PP eradication rate was 95% (95% CI: 93%‐96%), with moderate heterogeneity ( I 2 = 64%, P < 0.001: Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a similar eradication rate was observed when this therapy was used as a rescue therapy, from a second-line to sixth-line treatment, as reported previously. [21][22][23][24] This is higher than the rates of eradication achieved by treatment regimens established previously using triple therapies. 16 In general, the loss of effectiveness of these precious therapies has been associated with bacterial resistance to antibiotics, mainly to clarithromycin or metronizadole.…”
Section: Multivariable Analysismentioning
confidence: 98%
“…68 이 연구에서 제균 실패의 독립 위험인자는 치주염과 복약 순응도였다. 68 단일제형 캡슐법은 BMT 사제요법의 까다로운 복약 방법을 개선하기 위하여 PPI와 함께 BMT, MNZ, TTC을 하나의 캡슐 형태로 만든 단일제형을 하루 3회 복용하게 하는 간편한 방법 으로, 349명을 대상으로 한 다기관 후향적 연구에서는 94%의 제균율을 보여주었고, 69 6,482명이 포함된 메타분석에서 ITT 분석으로 제균율이 90%에 달하였다. 37…”
unclassified